Caudal mesopallial neurons in female songbirds bridge sensory and motor brain regions. Issue 10 (17th April 2018) - Dunning, Jeffery L.; Maze, Sarah E.; Atwood, Ethan J.; Prather, Jonathan F.
Abstract: Female songbirds use male song as an indicator of fitness and use that information to select their mate. Investigations of the female auditory system have provided evidence that the neurons within the caudal mesopallium (CM) are involved in the processing of songs that a female finds attractive, however, it is not clear how CM may exert its influence on behavioral indicators of mate choice. In the present study, anterograde tracing revealed the efferent connections of the female songbird CM. The results demonstrate connections to other auditory regions previously described in males, as well as novel connections to brain regions implicated in motor control. As in males, CM neurons in females project robustly to the lateral and medial extents of the caudal nidopallium, and to the ventral intermediate arcopallium. In a novel finding that is not present in males, CM neurons also project to the robust nucleus of the arcopallium and to the caudal striatum. Calling behavior and the expression of copulation solicitation displays are key indicators of female mate choice, and the projections found here bridge critical gaps necessary to understand how auditory perception can influence circuits related to the expression of those affiliative behaviors in female songbirds. Abstract : Efferent pathways from a sensory cortical area (CM) project to other cortical areas and downstream motor sites that control behavioral indicators of female mate preference. These pathways provide a mechanism through which perception‐related activity in CM may influence motor execution of songbird courtship behaviors and mate choice.